2017
DOI: 10.1007/s00464-017-5508-y
|View full text |Cite
|
Sign up to set email alerts
|

Optimal targeting of sympathetic chain levels for treatment of palmar hyperhidrosis: an updated systematic review

Abstract: Cumulative data from more than 13,000 patients suggest that ETS is a safe, effective, and reproducible procedure with a high degree of patient satisfaction. Currently available evidence suggests that T2-free ETS may reduce the incidence of compensatory hyperhidrosis without compromising success rates and safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 103 publications
1
13
0
1
Order By: Relevance
“…Also, disruption just cranial to the third rib produces the highest success rate in treating primary palmar and craniofacial hyperhidrosis. In another systematic review, the authors found that T2-free interventions lowered the risk of Horner's syndrome without compromising efficacy [ 18 ]. However, these conclusions are all based on retrospective reports, mainly in the adult population, and should be validated in prospective controlled trials.…”
Section: Discussionmentioning
confidence: 99%
“…Also, disruption just cranial to the third rib produces the highest success rate in treating primary palmar and craniofacial hyperhidrosis. In another systematic review, the authors found that T2-free interventions lowered the risk of Horner's syndrome without compromising efficacy [ 18 ]. However, these conclusions are all based on retrospective reports, mainly in the adult population, and should be validated in prospective controlled trials.…”
Section: Discussionmentioning
confidence: 99%
“…While others believed that the extent of resection had no effect on the occurrence of CH (23,24). Although plenty of studies have paid attention to the sympathetic levels (25)(26)(27)(28), the optimal sympathetic levels are still controversial. To determine which sympathetic surgical technique makes the lowest incidence of CH after surgery, we performed this meta-analysis.…”
Section: Commentsmentioning
confidence: 99%
“…The clinical implication of this study is that with the high incidence of CS reported in this study and our previous study, 17 which can be associated with the involvement of T2 resection, it may be proposed to our institute regarding reducing ETS surgery that involves T2 resection. This suggestion is backed by the literature, which claims that symptom resolution was not significantly different between T2-involved and T2-spared group, but incidence of CS was significantly higher in the T2-involved group 26,36 . In addition, the expert consensus 35 of The Society of Thoracic Surgeons also supported the idea that ETS should avoid involving the T2 level as it may result in more complications and significantly higher risk of CS.…”
Section: Discussionmentioning
confidence: 92%
“…In our centre, majority of BETS were performed at a level of T2-T3 (78.3%), the frequency reported is summarised in Table 3. A T2 level has been well recognised to increase the risk of CS and other complications if interrupted 26,27 . Hence, we further categorise patients into T2-involved and T2-spared group to study the difference between both groups.…”
Section: Level Of Sympathectomymentioning
confidence: 99%